Zinc and Copper Brain Levels and Expression of Neurotransmitter Receptors in Two Rat ASD Models - Zieminska, Elzbieta; Ruszczynska, Anna; Augustyniak, Justyna; Toczylowska, Beata; Lazarewicz, Jerzy W. (Frontiers in Molecular Neuroscience, 2021)
Zinc and copper are important trace elements necessary for the proper functioning of neurons. Impaired zinc and/or copper metabolism and signaling are implicated in many brain diseases, including autism (ASD). In our studies, autistic-like behavior in rat offsprings was induced by application to pregnant mothers valproic acid or thalidomide. Zinc and copper contents were measured in serum and brain structures: hippocampus, cerebral cortex, and cerebellum. Our research shows no interconnections in the particular metal concentrations measured in autistic animal brains and their sera. Based on patient researches, we studied 26 genes belonging to disturbed neurotransmitter pathways. In the same brain regions, we examined the expression of genes encoding proteins of cholinergic, adrenergic, serotonin, and dopamine receptors. In both rats’ ASD models, 17 out of the tested gene expression were decreased. In the cerebellum and cerebral cortex, expression of genes encoding cholinergic, adrenergic, and dopaminergic receptors decreased, whereas in the hippocampus only expression of serotoninergic receptors genes was downregulated. The changes in metals content observed in the rat brain can be secondary phenomena, perhaps elements of mechanisms that compensate for neurotransmission dysfunctions.